EFEITO DO ETHEPHON NA MATURAÇÃO E PRODUTIVIDADE DA CANA-DE-AÇÚCAR - Castro, Paulo R. C.; Miyasaki, João M.; Bemardi, Marcos; Marengo, Dalcides; Nogueira, Maria C. S. (REVISTA DE AGRICULTURA, 2015)
EFEITO DO ETHEPHON NA MATURAÇÃO E PRODUTIVIDADE DA CANA-DE-AÇÚCAR